Cytological, molecular, cytogenetic, and physiological characterization of a novel immortalized human enteric glial cell line - Zanoletti, Lisa; Valdata, Aurora; Nehlsen, Kristina; Faris, Pawan; Casali, Claudio; Cacciatore, Rosalia; Sbarsi, Ilaria; Carriero, Francesca; Arfini, Davide; van Baarle, Lies; De Simone, Veronica; Barbieri, Giulia; et al. (Frontiers in Cellular Neuroscience, 2023)
Enteric glial cells (EGCs), the major components of the enteric nervous system (ENS), are implicated in the maintenance of gut homeostasis, thereby leading to severe pathological conditions when impaired. However, due to technical difficulties associated with EGCs isolation and cell culture maintenance that results in a lack of valuable in vitro models, their roles in physiological and pathological contexts have been poorly investigated so far. To this aim, we developed for the first time, a human immortalized EGC line (referred as ClK clone) through a validated lentiviral transgene protocol. As a result, ClK phenotypic glial features were confirmed by morphological and molecular evaluations, also providing the consensus karyotype and finely mapping the chromosomal rearrangements as well as HLA-related genotypes. Lastly, we investigated the ATP- and acetylcholine, serotonin and glutamate neurotransmitters mediated intracellular Ca2+ signaling activation and the response of EGCs markers (GFAP, SOX10, S100β, PLP1, and CCL2) upon inflammatory stimuli, further confirming the glial nature of the analyzed cells. Overall, this contribution provided a novel potential in vitro tool to finely characterize the EGCs behavior under physiological and pathological conditions in humans.